Novel homozygous nonsense mutations in LHCGR lead to empty follicle syndrome and 46, XY disorder of sex development. Issue 7 (15th June 2018) - Chen, C; Xu, X; Kong, L; Li, P; Zhou, F; Zhao, S; Xin, X; Tan, J; Zhang, X
Abstract: Empty follicle syndrome (EFS) is a disorder associated with female infertility and presents as a complete failure to retrieve oocytes during ART cycles despite normal follicle development and careful aspiration. To date, only two EFS cases have been reported with homozygous missense mutations in the luteinizing hormone/chorionic gonadotropin receptor ( LHCGR ) gene, and both cases showed normal estradiol (E2) production during ovulation induction. The molecular genetic mechanisms of EFS remain unknown. Herein, we report two novel homozygous inactivating LHCGR mutations, c.736 C>T (p.Q246*) and c.846dupT (p.R283*), in two female EFS patients from unrelated consanguineous families. The probands had impaired E2 production during the ART process, which differs from previously reported EFS cases. The inactivating mutations not only led to EFS in the two female probands, but also resulted in 46, XY disorder of sex development (46, XY DSD) in their male siblings. As far as we know, this is the first report of LHCGR mutations leading to both EFS and 46, XY DSD within the same pedigree. Our findings provide researchers and clinicians with a better understanding of phenotype–genotype correlations between EFS and 46, XY DSD and the LHCGR gene.